Reperfusion-induced myocardial dysfunction is prevented by endogenous annexin-A1 and its N-terminal-derived peptide Ac-ANX-A1(2-26) - Qin, Chengxue (Blackwell Publishing Ltd, 2013)
BACKGROUND AND PURPOSE: Annexin-A1 (ANX-A1) is an endogenous, glucocorticoid-regulated anti-inflammatory protein. The N-terminal-derived peptide Ac-ANX-A1(2–26) preserves cardiomyocyte viability, but the impact of ANX-A1-peptides on cardiac contractility is unknown. We now test the hypothesis that ANX-A1 preserves post-ischaemic recovery of left ventricular (LV) function. EXPERIMENTAL APPROACH: Ac-ANX-A1(2–26) was administered on reperfusion, to adult rat cardiomyocytes as well as hearts isolated from rats, wild-type mice and mice deficient in endogenous ANX-A1 (ANX-A1(–/–)). Myocardial viability and recovery of LV function were determined. KEY RESULTS: Ischaemia–reperfusion markedly impaired both cardiomyocyte viability and recovery of LV function by 60%. Treatment with exogenous Ac-ANX-A1(2–26) at the onset of reperfusion prevented cardiomyocyte injury and significantly improved recovery of LV function, in both intact rat and wild-type mouse hearts. Ac-ANX-A1(2–26) cardioprotection was abolished by either formyl peptide receptor (FPR)-nonselective or FPR1-selective antagonists, Boc2 and cyclosporin H, but was relatively insensitive to the FPR2-selective antagonist QuinC7. ANX-A1-induced cardioprotection was associated with increased phosphorylation of the cell survival kinase Akt. ANX-A1(−/−) exaggerated impairment of post-ischaemic recovery of LV function, in addition to selective LV FPR1 down-regulation. CONCLUSIONS AND IMPLICATIONS: These data represent the first evidence that ANX-A1 affects myocardial function. Our findings suggest ANX-A1 is an endogenous regulator of post-ischaemic recovery of LV function. Furthermore, the ANX-A1-derived peptide Ac-ANX-A1(2–26) on reperfusion rescues LV function, probably via activation of FPR1. ANX-A1-based therapies may thus represent a novel clinical approach for the prevention and treatment of myocardial reperfusion injury.